The Big End of Town Meets the Local Council: The Investment Habitus of Four Sets of Australian Councils during the GFC. Issue 4 (5th September 2016) - Jones, Greg; Beattie, Claire; Bowrey, Graham; Smark, Ciorstan
Abstract : The Global Financial Crisis of 2008 led to a substantial write‐down in the value of investments such as collateralised debt obligations (CDOs) with one class of investors being NSW Local councils. This article analyses interviews with four different investor types (or sets) of local councils, each of which took a substantially different approach to CDO investment. This categorisation into sets was based on interviews of 28 individuals working within 14 local councils as well as commentaries on legal cases involving a class action of local councils suing Lehman Brothers Australia as well as Grange Securities over losses in their investments. This article adopts Bourdieu's Theory of Practice to describe and explain behaviour regarding decisions to invest (or not) in CDOs. Interesting themes arise regarding differing views on the appropriate role of local councils, and on the degree and form of 'capital' (which includes knowledge, competencies, skills, and economic resources) that a council should have before investing in sophisticated financial products. This article explores the role that field, habitus, and capital played in moderating and influencing council investment making decisions. The analysis shows that these Bourdieuian concepts can be utilised to help explain individual behaviour. This case study shows that excessive capital left in the hands of individuals may result in suboptimal decision making. Local councils may need to consider ways of implementing policies and procedures that can be used to moderate individual action. Abstract : This paper explores the role that field, habitus and capital played in moderating and influencing council investment making decisions. The analysis shows that these Bourdieuian concepts can be utilised to help explain individual behaviour. This case study shows that excessive capital left in the hands of individuals may result in suboptimal decision making. Local councils may need to consider ways of implementing policies and procedures which can be used to moderate individual action.